2021
DOI: 10.3390/biology10090943
|View full text |Cite
|
Sign up to set email alerts
|

Response to Climate Change: Evaluation of Methane Emissions in Northern Australian Beef Cattle on a High Quality Diet Supplemented with Desmanthus Using Open-Circuit Respiration Chambers and GreenFeed Emission Monitoring Systems

Abstract: The main objective of this study was to compare the effect of supplementing beef cattle with Desmanthus virgatus cv. JCU2, D. bicornutus cv. JCU4, D. leptophyllus cv. JCU7 and lucerne on in vivo methane (CH4) emissions measured by open-circuit respiration chambers (OC) or the GreenFeed emission monitoring (GEM) system. Experiment 1 employed OC and utilized sixteen yearling Brangus steers fed a basal diet of Rhodes grass (Chloris gayana) hay in four treatments—the three Desmanthus cultivars and lucerne (Medicag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…These changes lead to a balance away from acetate towards propionate as evidenced by reductions in acetate:propionate ratios resulting in a reduction in H 2 production due to utilisation for propionate formation. In this experiment, as with many forage-based studies (Rira et al 2015;Perry et al 2017;Suybeng et al 2020Suybeng et al , 2021, the shift in the acetate:propionate ratio was small but consistent with the changes in NDF content of the diet.…”
Section: Possible Causes For Methane Reductionsupporting
confidence: 84%
See 1 more Smart Citation
“…These changes lead to a balance away from acetate towards propionate as evidenced by reductions in acetate:propionate ratios resulting in a reduction in H 2 production due to utilisation for propionate formation. In this experiment, as with many forage-based studies (Rira et al 2015;Perry et al 2017;Suybeng et al 2020Suybeng et al , 2021, the shift in the acetate:propionate ratio was small but consistent with the changes in NDF content of the diet.…”
Section: Possible Causes For Methane Reductionsupporting
confidence: 84%
“…Suybeng et al (2020) observed a reduction in methane yield when poor-quality Rhodes grass was fed with increasing proportions of the tannin-containing tropical legume Desmanthus. However, in a subsequent study where diets were isonitrogenous (10% CP, 68% NDF), by substituting Desmanthus with lucerne, no effect on methane yield was observed (Suybeng et al 2021). In both studies, total phenolics (as catechin equivalents) were similar (1.2-2.3% DM).…”
Section: Effect Of the Basal Diet On Methane Responsementioning
confidence: 83%
“…The observed similar CP composition between cultivars in this study agrees with the findings reported by Suybeng et al [51] for JCU2, JCU4 and JCU7, and Amben et al [52] for JCU2 and JCU4. The decrease in desmanthus CP with an increase in maturity for both leaf and stem proportions observed in this study agree with findings reported by Suksombat and Buakeeree [42] for D. virgatus harvested at 30, 40 or 50 days regrowth and may be due to an increase in the fibre portion of the plant [53].…”
Section: Chemical Compositionsupporting
confidence: 93%
“…The authors attributed the findings to higher polyphenolic secondary compounds in JCU1. Significantly higher total tannins were recorded for JCU1 compared to JCU2 and JCU4 [18], while total phenolics were reported to be higher in JCU7 compared to JCU2 [51]. The potentially degradable DM (B) proportion declined by 36.7%, 20.8% and 11.9% for JCU4, JCU2 and JCU7, respectively, from day 78 to day 168 in this study resulting in the overall highest B degradability in JCU7.…”
Section: Dry Matter Degradabilitymentioning
confidence: 56%
“…Northern Australian native pastures are characterized by poor nutritive value, low digestibility and high fibre content ( Suybeng et al., 2019 ; Suybeng et al., 2020 ; Suybeng et al., 2021a ; Suybeng et al., 2021b ). McCosker et al., (2020) monitored the reproductive performance of commercial northern Australia beef breeding herds and found that substantial opportunities to increase reproductive performance exist, if the causes of variation are able to be identified and alleviated.…”
Section: Maternal Nutrition Foetal Development and Bullsmentioning
confidence: 99%